Organocatalytic γ′[C(sp3)–H] Functionalization of Ynones: An Unusual Approach for the Cyclopentannulation of Benzothiophenes - Grover, Jagdeep; Raghu, Moluguri; Hazra, Raju; Mondal, Atanu; Ramasastry, S. S. V. (Synthesis, 2018)
An efficient organocatalytic approach for the cyclopenta[b]annulation of benzothiophenes via γ′[C(sp3)–H] functionalization of ynones is described. Nucleophilic addition of an organophosphine to the designed ynones generates heteroaryl-based ortho-quinodimethanes (oQDMs), which undergo carbocyclization to provide a variety of cyclopenta-fused benzothiophenes. This approach also constitutes an unusual organophosphine-catalyzed intramolecular hydroalkylation of ynones.
Keywords: organophosphines; hydroalkylation; cyclopentannulation; ynones; benzothiophenes